2017
DOI: 10.1111/anu.12512
|View full text |Cite
|
Sign up to set email alerts
|

Digestibility of nutrients and energy in ingredients for bullfrogs during different phases of development

Abstract: The ability of frogs to digest dietary nutrients changes with growth, with the animals becoming more or less demanding. The objective of this study was to determine the apparent digestibility coefficients of protein, energy and ether extract of 14 ingredients used in bullfrog diets (spray-dried blood meal, hydrolysed feather meal, poultry by-product meal, red blood cell concentrate, tilapia by-product meal, sardine fishmeal, salmon fishmeal, meat and bone meal, corn gluten meal, soybean meal, corn, wheat bran,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 60 publications
1
4
0
Order By: Relevance
“…On the other hand, protein digestibility in this study was relatively low, possibly due to the ingredients utilised in the diets. Values obtained from the lipogenic diet agreed with diets including feather (55.1%), and sardine meal (54.4%) [16]. Conversely, shrimp meal (the major ingredient of the diets in the present study) has shown 65% protein digestibility in vitro , as well as 22% chitin digestibility [56]; ingredient composition may have resulted in the low coefficients obtained through poor digestibility of the shrimp exoskeleton constituent [57].…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…On the other hand, protein digestibility in this study was relatively low, possibly due to the ingredients utilised in the diets. Values obtained from the lipogenic diet agreed with diets including feather (55.1%), and sardine meal (54.4%) [16]. Conversely, shrimp meal (the major ingredient of the diets in the present study) has shown 65% protein digestibility in vitro , as well as 22% chitin digestibility [56]; ingredient composition may have resulted in the low coefficients obtained through poor digestibility of the shrimp exoskeleton constituent [57].…”
Section: Discussionsupporting
confidence: 62%
“…Fat digestibility agreed with previously-reported values for R . catesbeiana frogs fed diets based on poultry by-products, meat and bone, as well as soybean meals [16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During the six month trials, animals were fed three times per week a pelleted diet made in the Laboratory of Animal Nutrition, composed of shrimp meal (66.0%), soy bean meal (30.25%), calcium phosphate (0.75%), beef fat (1%), multivitamin supplement (0.50%) and rice syrup (1.5%). The composition of this diet was based on studies performed in bullfrogs, Rana ( Lithobates ) catesbeiana (Silva et al., 2014; Mansano et al, 2016; Zhang et al, 2015). The nutrient composition of the diet is presented in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…In raniculture, commercial feed is usually used for carnivorous fish with average levels of 45% crude protein [42]. In addition to the increase in the amount of feed offered according to the growth of the animals, there is also a change in the use of this feed in each developmental stage of the animal [43].…”
Section: Qualitative and Microbiological Characteristics Of Ranicultumentioning
confidence: 99%